Bmsage is involved in the determination of cell number in the silk gland of Bombyx mori. (October 2019) - Hou, Sihan; Sun, Yan; Wu, Yangchun; Cheng, Tingcai; Liu, Chun
Abstract: The number of cells in tissues is under strict genetic control, and research on the determination of cell number is of great importance to understand the growth and development of organs. Bmsage, a bHLH transcription factor, is involved in the development of the silk gland during the embryonic stage in Bombyx mori . However, the mechanism by which it influences silk gland development is unclear. In the present study, we determined via immunofluorescence staining during the embryonic stage of Bombyx mori that Bmsage is expressed in silk gland cells from the beginning of development of the silk gland until its complete formation. By comparing different silkworm strains, we found that Bmsage expression is positively correlated with the number of silk gland cells. Bmsage knockdown by RNAi resulted in shorter silk glands and lower cell numbers, especially in the posterior silk gland. The silk gland lumen also shriveled, and the silk protein content was significantly lower than that in the control. Further investigation revealed that all cyclins decreased after knock down of Bmsage, and cyclin B and cyclin 3 were significantly down-regulated. Bmsage may be involved in the regulation of the cyclin pathway to control silk gland development. Taken together, it can be concluded from our results that Bmsage is involved in the determination of cell number in silk glands. Our results help clarify the process of cell number determination in silk gland and identify a potential target for silkworm breeding. Graphical abstract: Image 1 Highlights: Bmsage is specifically expressed in silk glands at the embryonic stage. Bmsage knockdown results in a decrease in cell number in the silk gland. Bmsage determines cell number via the cyclin pathway in the silk gland. Sage regulates different pathways in the silkworm and the fruitfly.